Is a gluten-free diet sufficient in the treatment of Duhring’s Disease? - A Review - Zwardoń, Jakub; Kapciak, Alicja; Górny, Julia; Witas, Gabriela; Hawajski, Artur; Jankowska, Natalia; Kamieniecka, Oliwia; Naja, Katarzyna; Świerzyńska, Adrianna (Quality in Sport, 2024)
Introduction Dermatitis herpetiformis is a chronic autoimmune blistering disease characterized by intensely pruritic, symmetrically distributed skin lesions and an association with gluten-sensitive enteropathy. Despite advances in diagnostic methods, delayed diagnosis remains a challenge due to its overlapping features with other dermatoses. Aim of Study This study aims to provide a comprehensive overview of the diagnostic methods, associated conditions, and differential diagnosis of dermatitis herpetiformis, focusing on recent advancements in serological, histopathological, and immunological testing. Material and methods A comprehensive review of the literature on dermatitis herpetiformis was performed using the PubMed database. Results and Conclusions Direct immunofluorescence remains the gold standard in diagnosing dermatitis herpetiformis, revealing granular IgA deposits in the dermal papillae. Histopathological findings are supportive but nonspecific, with early lesions showing subepidermal vesicles and neutrophilic infiltrates. Serological markers, including anti-TG2 and anti- TG3 antibodies, provide valuable diagnostic support but exhibit variable sensitivity. HLA-DQ2/DQ8 haplotypes are present in most dermatitis herpetiformis patients, offering high negative predictive value for exclusion. Associated autoimmune conditions, such as autoimmune thyroid disease and type 1 diabetes, are prevalent, and dermatitis herpetiformis patients face an elevated risk of non-Hodgkin lymphoma within the first five years after diagnosis. The diagnosis of dermatitis herpetiformis relies on a combination of direct immunofluorescence, serological testing, and clinical features. Increased awareness of dermatitis herpetiformis and its associated conditions is critical for timely diagnosis and management. Advances in immunological and genetic testing may further refine diagnostic accuracy, while screening for associated autoimmune disorders and malignancies remains an integral part of patient care.